TARGETED THERAPIES AND CHEMOTHERAPY COMBINATIONS IN THE TREATMENT OF COLON CARCINOMA: ADVANCEMENTS, CHALLENGES, AND FUTURE PROSPECTS - Kuldeep Saharawat; Mamta Rani; Hemant Krishan Daiya (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Colon carcinoma remains a major health concern globally, with chemotherapy being a primary treatment approach. However, traditional chemotherapy often faces limitations, including drug resistance, toxicity, and non-specific targeting, which affect patient outcomes. Recent advancements have focused on integrating targeted therapies with chemotherapy, allowing for more personalized treatment regimens tailored to specific genetic mutations, such as KRAS, BRAF, and mismatch repair status, which influence responsiveness to therapy. Colon cancer incidence in India varies, with ASIR ranging from 3.5 to 5.1 per 100,000 for males and 2.7 to 3.7 for females across cities (NCRP, 2012–2014). GLOBOCAN 2020 reports slightly higher rates in males (4.4) than females (3.9). Studies highlight its significant cancer burden, late-stage diagnosis, and the need for early detection and awareness efforts. This review examines the evolution of chemotherapy in combination with targeted therapies, highlighting key advancements, such as molecular profiling, that guide treatment selection and improve efficacy. Additionally, it discusses the ongoing challenges, including the development of chemotherapy resistance, managing side effects, and the need for biomarkers to predict patient responses more accurately. The review concludes with an exploration of future prospects, such as novel drug delivery systems and immunotherapy-chemotherapy combinations currently under investigation. Through a comprehensive understanding of both the advancements and limitations of current approaches, this review provides insights into enhancing treatment outcomes and improving quality of life for patients with colon carcinoma.